Traffic noise influence on road network planning in Portugal - Cecília Rocha (2007)
This paper analyses the evolution of the Portuguese planning system (land use management and road network) along with the evolution of population's environmental awareness, especially regarding traffic noise. Until 2000, the ineffectiveness of noise legislation and the demographic movements towards the coastline, in conjunction with the European funding, created the adequate conditions to the development of Portuguese road network. In November 2000, a new Noise Code was approved which enforced municipalities and infrastructures Authorities to take the appropriate measures to reduce noise levels wherever they exceed the legal noise limits and to create zoning maps, noise maps and noise conflict maps.